2008
DOI: 10.1248/bpb.31.1192
|View full text |Cite
|
Sign up to set email alerts
|

NMR Metabolomic Analysis of Fecal Water from Subjects on a Vegetarian Diet

Abstract: Plant based food contains a multiplicity of bioactive phytochemicals. These compounds are believed to contribute to the cancer protective effect of a diet high in fruit and vegetables.1,2) One group of phytochemicals is the cyclooxygenase-2 (COX-2) inhibitors, which potentially can act as preventive agents against colon cancer. Such compounds and their derivatives may pass through the digestive system and reach the colon where they exert chemopreventive effects.The water fraction of feces (fecal water) is beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 62 publications
1
18
0
1
Order By: Relevance
“…Colonic derivatives of the flavonoids in the colon were detected at concentrations up to two orders of magnitude higher than these of their precursors; thus, the total monophenolic acids reached up to 740.7 mol and the total nonphenolic aromatic acids, 1.5 mmol [48] . Recent analyses of fecal water have confirmed the prevalence of the phenolic and non-phenolic aromatic acids in fecal water [28,54] . Therefore, our question of how polyphenols and their metabolites modulate the activity of butyrate may need to be re-stated to how the activity of butyrate is affected by high levels of monophenolic and nonphenolic acids.…”
Section: Synergistic or Antagonistic Effects Of Butyrate And Polyphenmentioning
confidence: 96%
See 1 more Smart Citation
“…Colonic derivatives of the flavonoids in the colon were detected at concentrations up to two orders of magnitude higher than these of their precursors; thus, the total monophenolic acids reached up to 740.7 mol and the total nonphenolic aromatic acids, 1.5 mmol [48] . Recent analyses of fecal water have confirmed the prevalence of the phenolic and non-phenolic aromatic acids in fecal water [28,54] . Therefore, our question of how polyphenols and their metabolites modulate the activity of butyrate may need to be re-stated to how the activity of butyrate is affected by high levels of monophenolic and nonphenolic acids.…”
Section: Synergistic or Antagonistic Effects Of Butyrate And Polyphenmentioning
confidence: 96%
“…To date, there are two approaches that address these problems: (1) performing analyses with the aqueous phase of feces (fecal water); and (2) utilizing in vitro GI models. The first approach is justified by the fact that the colonic epithelium is exposed to the fecal matter in vivo [48,[51][52][53][54] and that fecal water affects the growth of colonocytes more effectively than components of the solid phase of feces [52,53] . Gas chromatography and mass spectrometry analyses of the fecal water of healthy volunteers have identified and quantified the flavonoids and their derivatives in the colon [48] .…”
Section: Use Of Fecal Watermentioning
confidence: 99%
“…It has been shown that intact fecal water (water phase) samples from human volunteers significantly decreased prostaglandin production and COX-2 expression in colonic cells. NMR spectroscopy and multivariate data analysis were later used for further analysis of the composition of the fecal waters and to trace the COX-2 inhibiting activity [18,19]. The wealth of different natural products with experimentally demonstratedCOX inhibitory effects and an urge to understand and characterize their structural diversity was the starting point for the application of chirography in our natural products research.…”
Section: Natural Products With Anti-inflammatory and Anti-tumor Activitymentioning
confidence: 99%
“…Metabolite profiling of fecal extracts is not a simple analysis since feces are a complex mixture of digested and undigested food, bacterial fermentation products and metabolites, human cells and secretions, and microorganisms. Nuclear magnetic resonance (NMR) spectroscopy-based metabolomic analysis is a powerful technique that has been used to characterize the compositional metabolic profiles of feces [Bezabeh et al, 2009;de Graaf et al, 2010;Han et al, 2010;Jacobs et al, 2008;Monleon et al, 2009;Pettersson et al, 2008;Romick-Rosendale et al, 2009;Yap et al, 2008]. However, there are few studies on metabolomic approaches in feces that take account of the metabolic changes that occur during exposure to antibiotics and evaluate the effects of antimicrobial residues on the intestinal microbiota [Romick-Rosendale et al, 2009;Swann et al, 2011].…”
Section: Introductionmentioning
confidence: 99%